Influência da inflamação gengival na qualidade de vida relacionada à saúde bucal de indivíduos residentes em uma zona rural do sul do Brasil - Oliveira, Leandro Machado (2020)
The plaque induced gingival disease determines a negative influence on oral health-related quality of life (OHRQoL) in children and adolescents. However, the body of evidence in the adult population focuses on the relationship between periodontitis and OHRQoL, and there is no data regarding the independent association of the referred outcome related to gingival inflammation. Moreover, the disparities present in rural areas regarding access, self-perception and resilience in health reinforce the importance of studies in these regions, which are also scarce. The aim of this dissertation was to present an article that evaluated the influence of gingival inflammation, regardless of clinical and self-perceived sequelae of periodontitis, on OHRQoL in individuals living in rural areas of southern Brazil. The present study was derived from a representative sample (n = 688) of the population living in the rural area of Rosário do Sul, Rio Grande do Sul, Brazil. For the present analysis, 71 edentulous, 22 with less than 5 teeth, 4 who did not answer the OHRQoL questionnaire and 470 individuals with probing depth (PD) values greater than three millimeters were excluded; therefore, the subsample had 121 individuals. Participants were examined clinically for dental caries, periodontal diseases - six sites per tooth and all teeth excluding third molars – visible plaque, calculus, prosthesis use and tooth loss. Anthropometric measurements and blood collection for the measurement of glycated hemoglobin were also performed. Semi-structured socioeconomic questionnaires were applied to collect sociodemographic characteristics, behavioral to collect hygiene habits, smoking and use of dental services, and structured and validated questionnaires to measure self-perceived periodontal disease and stress and OHRQoL. Gingival inflammation was defined as the presence of more than 20% of sites in whole mouth and more than 10% of sites in the anterior region (all sites of elements 13 to 23 and 43 to 33) with bleeding on probing, measured by the Bleeding on Probing Index (BoP), and no site exceeding three millimeters of PD. The OHRQoL was measured by the reduced version of the validated Oral Health Impact Profile (OHIP-14) questionnaire. Contextual variables related to the districts were obtained from official publications of the municipality. The data were analyzed using Multilevel Poisson Regression Models with hierarchical approach to include variables. The findings confirm the hypothesis that gingival inflammation influences the OHRQoL of individuals living in a rural area of southern Brazil. Those individuals who had BoP in more than 20% of sites in whole mouth and more than 10% of the sites in the anterior region had worse OHIP-14 scores. These findings support the need to implement public policies not only for the conditions of greater periodontal severity, but also for the lesser ones.